Computed tomographic diaphragmatic thickness: a promising method for the evaluation of diaphragmatic muscle in cardiopulmonary diseased cats - Saisawart, Phasamon; Sutthigran, Somchin; Suksangvoravong, Hathaiphat; Thanaboonnipat, Chutimon; Ritthikulprasert, Sukullaya; Tachampa, Kittipong; Choisunirachon, Nan (Frontiers in Veterinary Science, 2023)
Diaphragmatic dysfunction (DD) is defined as a weakening of diaphragmatic muscle and can be an undetected cause of dyspnea. The objectives of this study were to explore the appropriate diaphragmatic location, to measure diaphragmatic thickness (DT), evaluate the effect of intrinsic factors on DT, and compare DT between healthy and diseased cats, using 33 healthy cats and 15 diseased cats. A retrospective, analytical, case-control study using thoraco-abdominal feline computed tomography (CT) was performed. Two radiologists independently reviewed all images to verify inter-and intra-observer reliabilities, and the best position for measuring DT. The effect of sex, age, and body weight were also studied, and cut-off values for detecting DT abnormalities were established. The results showed that the appropriate location for DT measurement was at the ventral border of the cranial end plate of the first lumbar vertebral body (L1) due to its highest intra-and inter-observer reliabilities. At this location, a significant difference of DT between the right and the left hemidiaphragm (P = 0.01) was observed. Only sex had an impact on DT values. Interestingly, the DTs of cardiorespiratory-affected cats, both on the right and left sides, were significantly thinner than those of healthy cats. In conclusion, CT image is a reliable imaging method for determining diaphragmatic muscular atrophy. The ventral border of the cranial end plate of L1 is recommended for measuring the DT, and sex was the only factor affecting the DT measurement.